EFFECTIVENESS OF ENDORPHINS MASSAGE AND ICE PACKS TO RELIEVE THE FIRST STAGE OF LABOR PAIN AMONG THE PREGNANT WOMEN IN CANDIMULYO HEALTH CENTER, INDONESIA - Mariza Mustika Dewi; Tuti Sukini; Nurul Aziza Ath Thaariq; Niken Wahyu Hidayati (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: More than 90% of women experience severe labor pain. Endorphin massage and applying ice packs have been well known as non-pharmacological methods for pain reduction faced during delivery. Aims: This study is to determine the effectiveness of endorphins massage and ice packs to the first stage of labor pain. Methods: This study was a quasi-experiment with non-equivalent control group and pretest-posttest design. This research involved 30 pregnant mothers at the first stage in Candimulyo Health Center, Indonesia. The labor pain level at the first stage was measured before and after the intervention either by endorphins massage or ice packs. Data from Visual Analog Scale (VAS) sheet was employed to define the labor level, and was then analyzed statistically using Mann-Whitney Test. Results: Either endorphin massage or ice pack application decreased the pain level among the pregnant women in Candimulyo Health Center, Indonesia, respectively, at difference level of 0.008 and 0.000. The number of mother experienced massive pain level decreased from 20% to 0% by given endorphin massage, and 13.3% to 6.7% after applying ice packs. In addition, in the group who received endorphin massage, 9 mothers declared having heavy labor pain, however, after the treatment, only 3 mothers declared the heavy labor. It also happened at the group who given ice pack application where the number of mother claimed heavy pain decreased from 10 to only 6. The results highlighted that the endorphin massage (18.50) is more effective to decreasing labor pain than the ice pack application (12.50), and the difference was significant (p value < 0.05). Conclusion: The highlight of endorphin massage and ice pack application in reducing the labor pain becomes evidence suggesting the other non-pharmacological methods as alternative treatments. The results shows the importance to provide endorphin massage and ice pack application for reducing labor pain among the pregnant women.